Kebijakan Pajak pada Masa Abu Yusuf : Konsep, Implementasi, dan Relevansi Terhadap Perekonomian di Indonesia - Gita Puji Lestari; Widya Siti Nabilah; Nabila Bilqis Mutiara; Lina Marlina (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
This study examines the tax policies during the time of Abu Yusuf, a prominent Islamic scholar and economist who significantly contributed to the Islamic financial system through his work Kitab al-Khara. The research aims to analyze Abu Yusuf's taxation concepts, their implementation during the Abbasid Caliphate, and their relevance to modern taxation systems, particularly in Indonesia. This study employs a qualitative method with a literature review approach. The findings indicate that Abu Yusuf favored a proportional tax system (muqasamah) over a fixed tax system (misahah), as it is fairer and more adaptable to economic fluctuations. He also emphasized the importance of tax officials' integrity, transparency in tax administration, and strict supervision of tax collectors to prevent corruption. This study highlights that Abu Yusuf’s taxation principles remain relevant in modern taxation systems, particularly in terms of fairness, efficiency, and fiscal transparency.